Optimasi Rute Pengiriman BBM dengan Heterogeneous Vehicle Routing Problem With Multi-Trips - Hasyrani Windyatri; Rozar Rayendra (G-Tech: Jurnal Teknologi Terapan, 2023)
Depot Fuel Oil X has many customers spread over several areas and delivers fuel to some gas stations using 3 different types of vehicles. The research aims to determine the optimal route to minimize the total distance traveled. As the total distance traveled is reduced, the product delivery time is expected to be shorter. To overcome this problem, the Heterogeneous Vehicle Routing Problem (HVRP) is applied by considering whether a vehicle can make more than one trip in one working day (multi-trip). The model used is Mixed Integer Linear Programming (MILP) with several variants: determining routes based on clusters, multi-trip, vehicle types, and road classes, and solving problems using the branch and bound method on the LINGO solver. The results obtained showed that the route optimization for Cluster 1 decreased the total mileage by 6.55%, for Cluster 2 reduced by 23.84%, and for Cluster 3 decreased by 9, 57%.